Tapping into Tinospora crispa and Tinospora cordifolia bioactive potentials via antioxidant, antiglycation and GC-MS analyses - Luqman Jaya,; Zunika Amit,; Teknowilie Singa,; Okechukwu, Patrick N.; Mohamad Johari Ibahim,; Aisha Mohd Din,; Froeming, Gabriele R.A (Penerbit Universiti Kebangsaan Malaysia, 2024)
Tinospora crispa and Tinospora cordifolia are plant species that are commonly used in traditional medicine, such as Ayurvedic medicine, renowned for their therapeutic roles in addressing diverse health issues, including diabetes. These plants are esteemed for their ability to counter oxidative stress through electron donation which is a prominent feature of antioxidants. However, a sole assessment of their antioxidant effectiveness is insufficient to holistically understand their antioxidative capabilities. This study aimed to study the antioxidative and antiglycation properties exhibited by T. crispa and T. cordifolia. This evaluation encompassed a range of tests measuring radical scavenging activity (DPPH assay), capacity for reducing ferric ions (FRAP assay), and their antiglycation potential (BSA-MGO assay). GC-MS analysis was employed to identify compounds with antioxidative properties within T. crispa and T. cordifolia. The stems and leaves of T. crispa and T. cordifolia underwent solvent extraction using 90% methanol and hot distilled water. Notably, the methanolic extract of T. cordifolia displayed the most robust radical scavenging activity, evident from its lowest IC50 value, 0.03 ± 0.00 mg/mL in the DPPH assay. Conversely, the methanolic extract of T. crispa exhibited the lowest IC50 value, 0.19 ± 0.00 mg/mL in the FRAP assay. Additionally, the methanolic extract of T. cordifolia showcased a minimal IC50 value of 0.52 ± 0.18 mg/mL in the BSA-MGO antiglycation assay. It’s worth noting that the methanolic extracts of both T. crispa and T. cordifolia outperformed their hot water counterparts in terms of antioxidative activity, potentially due to the presence of phytochemical compounds such as phenol, 4-vinyl guaiacol, guaiacol, syringol, and vanillin in the methanolic extracts. The study highlights the potent antioxidative properties of T. crispa and T. cordifolia in supporting their traditional medicinal use and leads the way for the development of antioxidant therapies, particularly for managing oxidative stress-related conditions such as diabetes.